2021
DOI: 10.1021/acs.joc.1c02178
|View full text |Cite
|
Sign up to set email alerts
|

n-Butyllithium-Induced Tandem [3,3]-Sigmatropic Rearrangement and Carbonyl Olefination of Allyl-1,1-dichlorovinyl Ethers

Abstract: Exposure of dichlorovinyl ethers 1 to n-butyllithium and addition of saturated or unsaturated aldehydes, ketones, or esters at ambient temperature furnishes rearranged α,β-unsaturated carboxylic acids, isolated as their corresponding methyl esters 2 in 48–91% overall yields. Exposure of dichlorovinyl ethers 1 to n-butyllithium, addition of aldehydes, ketones, dialdehydes, or diketones at −78 °C, and warming to 80 °C in the presence of SiO2 provide 1,4-dienes 3 or cycloalken-1-ols (or their dehydration products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Therefore, [2 + 2] cycloaddition by the reaction of ynolates with acrylates can proceed if a convenient alkoxide-free preparation of ynolates is developed . Thus, this study investigated the generation of alkoxide-free ynolates from α,α,α-tribromomethyl ketones by a simple treatment with alkyl lithium.…”
mentioning
confidence: 99%
“…Therefore, [2 + 2] cycloaddition by the reaction of ynolates with acrylates can proceed if a convenient alkoxide-free preparation of ynolates is developed . Thus, this study investigated the generation of alkoxide-free ynolates from α,α,α-tribromomethyl ketones by a simple treatment with alkyl lithium.…”
mentioning
confidence: 99%
“…Finally, we have recently shown that allylic ynolates, 19–21 generated by base-induced [3,3]-sigmatropic rearrangement of allyl-1,1-dichlorovinyl ethers, undergo [2 + 2] cycloaddition reactions with carbonyl compounds to furnish unsaturated carboxylic acids. 22 Similarly, quenching the rearrangement reactions of 3 with ketones or sterically encumbered aldehydes 23 instead of methanol gave rise to complex unsaturated lactones 6 via a carbonyl-ynolate [2 + 2] cycloaddition followed by reaction of the resulting allenolate with a second equivalent of the aldehyde or ketone and translactonization. Lactone 6a (arising from dichlorovinyl ether 3a and acetone), lactone E - 6b (as a 1 : 1 mixture of diastereomers, arising from dichlorovinyl ether 3e and pivaldehyde) and lactone E - 6c (arising from dichlorovinyl ether 3c and cyclohexanone) were prepared in this fashion in 82, 61, and 59% yields, respectively.…”
mentioning
confidence: 99%